Religious Proximity and Cultural Distance: An Introduction on the East/West Dichotomy - Tite, Philip L. (Bulletin for the study of religion, 2015)
Editor's introduction to this issue of the Bulletin for the Study of Religion. Explores the East/West dichotomy in religious studies, situating the discussion within the framework of cultural and human geography (specifically processes of proximity and distance). Also introduces a two pieces related to the Bulletin's affiliation with NAASR (an interview with the new president, Russell McCutcheon, and the NAASR Notes).